Historical forest disturbance reduces soil microbial efficiency across multiple carbon sources. (February 2022) - Osburn, Ernest D.; McBride, Steven G.; Barrett, J.E.
Abstract: We measured the catabolic responses of soils to several classes of carbon (C) compounds to characterize the C metabolism of microbial communities in forest ecosystems subject to long-term disturbances at the USFS Coweeta Hydrologic Laboratory in North Carolina, USA. Catabolic profiles were distinct between reference and disturbed forest soils when adjusted to microbial biomass, reflecting higher biomass-specific respiration responses to all substrates in disturbed soils. However, only amino acid metabolism exhibited differences between land uses (i.e., disturbed > reference) when expressed as percentages of total C respired. Overall, we observed a general reduction in microbial efficiency across all substrates and greater overall metabolism of some substrates in disturbed soils. These results suggest that disturbed soil microbial communities could drive alterations to soil C cycling by altering the distribution of C amongst different pools in these forests. Highlights: Forest disturbance altered catabolic profiles when adjusted to microbial biomass Amino acids were metabolized in higher proportions by disturbed soil communities Microbial efficiency was lower for most substrates in disturbed soils